PERANCANGAN MEDIA INTERAKTIF LOGIKA PEMOGRAMAN UNTUK MENARIK MINAT BELAJAR SISWA PADA SMK NEGERI 1 MESJID RAYA - Muftizar Muftizar; Hendri Ahmadian; Basrul Abdul Majid (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2020)
This study aimed to design interactive learning media of Programming Logic using Adobe Flash CS6 applications, and determined the effect of student interest in those media. This research was conducted at SMK Negeri 1 Mesjid Raya which students of multimedia class X as the sample. The method of this study was the research and development area. There were several stages carried out for the research process, which started from the concept, design, material collection, process, testing and distribution. The technique of data collection used a questionnaire. This media application has been tested and validated by the experts of multimedia. The results of this study was the coefficients test obtained 2 variables that affect interest, namely the media and material. The effect of attracting students' learning interest using this media gets 52.7% results. Threfore, it can be concluded that interactive media programming logic can influence to attract students' learning interest.